The Effect of a Combination Cream Containing 4% Licorice Extract, 5% Tranexamic Acid, and Dexpanthenol in Liposome on Melanin Levels and Expression of Microphthalmia-associated Transcription Factor (MITF) in UV-B Exposed Rat (Rattus norvegicus) Skin - Jeanny Indriani; Diana Krisanti Jasaputra; Fen Tih (UPT Publikasi Ilmiah Universitas Islam Bandung, 2025)
Melanin synthesis is regulated by the microphthalmia-associated transcription factor (MITF), a crucial regulator of melanogenesis. The combination of licorice extract and tranexamic acid has been known to exhibit synergistic effects in addressing hyperpigmentation. Additionally, the inclusion of dexpanthenol in liposome formulations can enhance the absorption of topical drugs, improve their effectiveness, and reduce side effects associated with topical treatments. This study aimed to investigate the effects of a combination cream containing 4% licorice extract, 5% tranexamic acid, and dexpanthenol in liposomes on improving hyperpigmentation in UV-B-exposed Wistar rat skin, as assessed by melanin levels and MITF gene expression. This research was carried out in the laboratory of the Faculty of Medicine, Universitas Kristen Maranatha, and the Iratco Laboratory, Bogor, Indonesia, from April to December 2024. The results showed that the application of the combination cream significantly reduced melanin levels. In the treatment group, the lowest average melanin level was observed at 0.869±0.263, compared to 2.763±0.398 in the negative control group and 6.391±0.430 in the vehicle control group (p<0.0001). The combination cream also significantly reduced MITF expression, with the treatment group showing the lowest average MITF expression at 0.306±0.201, compared to 1.025±0.102 in the negative control group and 2.320±0.112 in the vehicle control group (p=0.000). It can be concluded that the combination cream containing 4% licorice extract, 5% tranexamic acid, and dexpanthenol in liposome effectively reduced melanin levels and MITF expression in UV-B-exposed Wistar rat skin.